Assessing the Performance of Public Sector Entities in Nepal: A Cash Flow Ratios Perspective - Adhikari, Naba Raj (Universitas Madura, 2024)
The aim of this study is to examine and analyze the financial performance of three Nepalese public enterprises - Nepal Electricity Authority (NEA), Nepal Oil Corporation (NOC) and Nepal Telecom (NTC) - using cash flow ratios as suggested by Giacomino & Mielke (1993). The study used judgmental sampling technique. Employing a descriptive and analytical research design, the study analyzes financial statements from 2020/2021 to 2022/2023. The analysis focus on sufficiency and efficiency ratios to assess the enterprises’ cash generation and management. Results indicate diverse financial performances: NTC shows strong cash flow, NEA moderate efficiency, and NOC significant financial distress with negative cash flow ratios. This research emphasizes the applicability of cash flow ratio analysis in evaluating the financial health of public enterprises in Nepal.